Empirical evidence on the impacts of bikesharing: a literature review. Issue 3 (4th May 2021) - Teixeira, João Filipe; Silva, Cecília; Moura e Sá, Frederico
ABSTRACT: In recent years, bikesharing has become one of the most popular policies promoting cycling across the world. As the number of bikesharing systems (BSS) continues to rise, it is increasingly important to quantify their expected benefits. This paper synthetises the available evidence on the current impacts of implementing a BSS, with a special focus on the induced modal shift dynamics and impacts in car reduction, indicating how increasing the attractiveness of BSS to car users could improve its benefits. Several benefits have been associated to bikesharing, but they are not equally distributed and are dependent on several nuances, particularly on modal shifts. Among the biggest contributions are the increases in physical activity (PA) levels (triggering health gains) as well as travel time savings to the BSS users. Bikesharing is mostly replacing sustainable modes of transport, with modest car replacing rates. However, bikesharing can also indirectly decrease car travel by fostering synergies with Public Transport (by expanding catchment areas, reducing overcrowding and overall travel times) and by promoting cycling use through increasing the number and diversity of cyclists. Furthermore, different types of modal shift lead to different benefits. Reductions in car travel induce decreases in greenhouse gases (GHG) and other air pollutants, increases in PA, time savings as well as congestion reductions. Conversely, new trips generated by BSS also lead to increases in PA, while modal shift from walking to BSS has been associated with travel time savings. Shifting PT users to BSS can also reduce overcrowding in saturated PT networks. The most social disadvantaged groups were found to be systematically under-represented among BSS users, yet equity measures combined with awareness-raising campaigns could increase usage rates. Exploring potential advantages of BSS against car use and increasing its car replacing rates, coupled with better impact assessments, should constitute research priorities.